2010
DOI: 10.1021/jm100438s
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Drug Design and Optimization of Mannoside Bacterial FimH Antagonists

Abstract: FimH-mediated cellular adhesion to mannosylated proteins is critical in the ability of uropathogenic E. coli (UPEC) to colonize and invade the bladder epithelium during urinary tract infection. We describe the discovery and optimization of potent small-molecule FimH bacterial adhesion antagonists based on α-D-mannose 1-position anomeric glycosides using X-ray structure-guided drug design. Optimized biaryl mannosides display low nanomolar binding affinity for FimH in a fluorescence polarization assay and sub mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
286
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(294 citation statements)
references
References 40 publications
6
286
0
2
Order By: Relevance
“…Initial studies showed that monovalent mannose derivatives display rather weak inhibitory effects (Firon et al 1987), but recent use of multivalent compounds with increased binding activity is promising success (Han et al 2010). Biphenyl mannosides were shown to be 200,000 fold more potent than the originally tested monovalent mannose.…”
Section: Page 7 Ofmentioning
confidence: 99%
“…Initial studies showed that monovalent mannose derivatives display rather weak inhibitory effects (Firon et al 1987), but recent use of multivalent compounds with increased binding activity is promising success (Han et al 2010). Biphenyl mannosides were shown to be 200,000 fold more potent than the originally tested monovalent mannose.…”
Section: Page 7 Ofmentioning
confidence: 99%
“…Prevention and treatment of urinary tract infection by UPEC requires orally active FimH antagonists, absorbed in the intestine and renally excreted, with finely tuned pharmacokinetic properties, so as to achieve an optimal balance between affinity and duration of the therapeutic effect in the bladder. This is typically pursued with monovalent aryl mannosides [13][14][15][16][17] targeted to the FimH binding site by their mannose component and carrying extended aromatic aglycones that establish high affinity interaction with the tyrosine gate (3-5, Figure 1a). Extensive medicinal chemistry programs are under way, including the use of prodrugs and bioisosters to achieve optimal pharmacological profile of these structures [18].…”
Section: Inhibitors Of Adherent-invasive and Uropathogenic E Colimentioning
confidence: 99%
“…6A). Additionally, it is believed that increased binding affinity of compounds can also be related to a decrease in conformational flexibility and thus a decrease in the entropic cost of binding (181)(182)(183).…”
Section: Fimh Antagonists: Mannosidesmentioning
confidence: 99%
“…Inhibition of epitope binding can be measured directly by examining the inhibition of the type 1-dependent hemagglutination of guinea pig red blood cells, which present mannosylated epitopes on the surface of the cell (181). Additional assays include inhibition of bacterial adherence to plastic plates that have been coated in mannosylated bovine serum albumin or inhibition of type 1-dependent adherence to human epithelial carcinoma bladder 5637 cells expressing mannosylated uroplakins (184,185).…”
Section: Fimh Antagonists: Mannosidesmentioning
confidence: 99%